Back-contact perovskite solar cells with honeycomb-like charge collecting electrodes. (August 2018) - Hou, Qicheng; Bacal, Dorota; Jumabekov, Askhat N.; Li, Wei; Wang, Ziyu; Lin, Xiongfeng; Ng, Soon Hock; Tan, Boer; Bao, Qiaoliang; Chesman, Anthony S.R.; Cheng, Yi-Bing; Bach, Udo
Abstract: Back-contact electrodes have been broadly applied to silicon photovoltaics to enhance their performance and avoid parasitic absorption from window materials and charge collection grids [1, 2]. Here we introduce an innovative back-contact design for perovskite solar cells (PSCs) derived from our recently described quasi-interdigitated back-contact architecture [3]. The back contact consists of a top electrode, which has a honeycomb-like grid geometry, that is separated from the underlying planar bottom electrode by a similarly shaped insulating Al2 O3 layer. This new design has higher structural robustness, as well as better defect tolerance, resulting in the highest short-circuit current (~ 16.4 mA/cm 2 ) and stabilized power output (~ 4%) for a back-contact PSC to date. The improved performance was attributed to an increased charge collecting efficiency, with photocurrent mapping revealing what electrode dimensions are required for optimum efficiency. Graphical abstract: fx1 Highlights: A new device configuration for back-contact perovskite solar cells is presented. The design features a defect tolerant honeycomb-like top electrode. The effect of electrode pitch size on device performance was revealed. Record short circuit currents and stabilized power outputs were achieved.